(untitled) (Physical Education, Health and Social Sciences, 2025)
Shrines in South Asia have historically functioned as spiritual sanctuaries and civic anchors, yet many are increasingly strained under rapid urbanization. The Mian Mir Shrine precinct in Lahore exemplifies this condition, where unregulated commercial encroachments, chronic traffic congestion, inadequate pedestrian infrastructure, and limited civic amenities have undermined both accessibility and the site’s sacred character. Within a 250-meter radius, the precinct reveals fragmented circulation systems, underutilized open spaces, and the absence of cohesive planning. This research advances a heritage-led regeneration framework that emphasizes sustainable mobility solutions, pedestrian-friendly circulation, inclusive community plazas, Mughal-inspired urban furniture, intuitive wayfinding systems, and resilient civic infrastructure. By positioning the shrine as a catalyst for sustainable and inclusive urban regeneration, the study illustrates how sacred heritage can guide governance strategies, enhance livability, and strengthen cultural identity. Beyond Mian Mir, the findings present a transferable model for revitalizing historic precincts facing similar pressures, contributing to global discourse on urban regeneration, heritage conservation, and sustainable city futures.